POLITIK HUKUM PERLINDUNGAN PEKERJA MIGRAN INDONESIA DALAM PERSPEKTIF FIKIH SIYASAH DUSTURIYAH - Hakim, Dani Amran; Havez, Muhammad (Faculty of Law, Tanjungpura University, 2020)
This article discusses the politics of law for Indonesian migrant workers protection. The aim of discussion is to understand the politics of law for Indonesian migrant workers protection in siyasah dusturiyah fiqh perspective based on Law Number 18 Year 2017 about Indonesian Migrant Workers Protection.The method used is literature review using a juridicial normative approach and content analyisis. The Article 3 of the Law on the Protection of Indonesian Migrant Workers states that Indonesian migrant workers protection aim to protect the human rights as well as to fulfil the legal, economic and social needs of migrant workers and their families. The protection is conducted before, during and after their working time. Based on the perspective of siyasah dusturiyah fiqh which is a part of siyasah fiqh that addresses the issue of legislation of state, so the Law on the Protection of Indonesian Migrant Workers is in accordance with 4 (fourth) principles of workers protection in Islam, they are 1) human independency; 2) human dignity; 3) justice; 4) contract (akad) and payment clarity.Tulisan dalam artikel ini membahas mengenai politik hukum perlindungan pekerja migran Indonesia. Tujuannya untuk mengetahui perspektif fikih siyasah dusturiyah terhadap perlindungan pekerja migran Indonesia berdasarkan Undang-Undang Nomor 18 Tahun 2017 tentang Perlindungan Pekerja Migran Indonesia.Metode yang digunakan adalah kajian pustaka dengan menggunakan pendekatan yuridis normatif dan analisis konten. Berdasarkan Pasal 3 Undang-Undang Perlindungan Pekerja Migran Indonesia memberikan arah tujuan yang hendak dicapai dalam perlindungan pekerja migran Indonesia yaitu menjamin pemenuhan dan penegakan hak asasi manusia para pekerja migran serta menjamin perlindungan hukum, ekonomi dan sosial pekerja migran serta keluarganya. Perlindungan tersebut dilaksanakan sebelum, selama dan setelah bekerja. Berdasarkan fikih siyasah dusturiyah, yang merupakan bagian fikih siyasah yang membahas masalah perundang-undangan negara, maka Undang-Undang Perlindungan Pekerja Migran Indonesia ditinjau dari perspektif tersebut sesuai dengan 4 (empat) prinsip ketenagakerjaan dalam Islam yaitu; 1) kemerdekaan manusia; 2) prinsip kemuliaan derajat manusia; 3) prinsip keadilan; dan 4) prinsip kejelasan akad (perjanjian) dan transaksi upah.